The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18502/kss.v7i1.10205
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Husbands' Social Support and Anxiety in Mothers Who Have Experienced Mom-Shaming in Malang City

Abstract: This research aimed to describe husbands’ social support and anxiety in mothers who have experienced mom-shaming in Malang city. A quantitative and descriptive correlational approach was used. The study aimed to determine whether there was a relationship between these two variables. Data were collected using The Husband’s Social Support Scale and The Mother’s Anxiety Scale. 118 women participated with the following characteristics: (a) mothers who have experienced mom-shaming; (2) mothers who have double roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The individuals or media sources expressing these messages regarding child screen time may have meant to help mothers. However, such input may be perceived by mothers as shaming those who allow screen time, which can adversely influence their mental health and subsequently impact the child [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individuals or media sources expressing these messages regarding child screen time may have meant to help mothers. However, such input may be perceived by mothers as shaming those who allow screen time, which can adversely influence their mental health and subsequently impact the child [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The support that working mothers get from their husbands will affect the conflict between work and family (Soeharto & Kuncoro, 2015). Research by Dawenan and Shanti (2021) found that the higher the husband's social support, the lower the mother's anxiety. The family dimension has the second highest average, followed by the friend dimension, meaning that mothers who work during the COVID-19 pandemic receive help and emotional support from their extended family.…”
Section: Discussionmentioning
confidence: 99%